Pembuatan Preparat Tumbuhan Sebagai Media Pembelajaran IPA Biologi Bagi Siswa SMP Negeri 7 SATAP Leihitu - Pesik, Anneke; Hiariej, Adriana; Kaihena, Martha; Riupassa, Pieter Agusthinus; Lapu, Petrus (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
Plant cell differentiation can only be understood visually by students through observation with a microscope. The ability of junior high school students to use microscopes is still limited so that practicum activities for making preparations are needed. This activity aims to improve student understanding and skills about monocular and binocular microscopes and making plant preparations to observe stomatal and epidermal cells. The implementation method includes lectures, interactive discussions, question and answer sessions, and making fresh plant preparations and proper microscope usage techniques. The results of the activity showed that participants were able to operate a microscope, make fresh plant preparations, and observe cells. The level of enthusiasm of the participants was quite high, especially when they managed to observe stomatal and epidermal cells directly through the microscope.